Urgensi implementasi three line of defense dalam industri perbankan syariah - Fitriani, Ika Lutfia (Maliki Interdisciplinary Journal, 2023)
The Islamic banking industry is one of the fastest growing financial sectors worldwide. The sustainability and health of this sector is very important to support sustainable economic growth. To achieve this goal, risk management in the Islamic banking industry is a key aspect that cannot be ignored. One approach that has been proven effective in managing risk is the implementation of the Three Lines of Defense (TLoD). This article discusses the urgency of implementing TLoD in the Islamic banking industry as a strategy to identify, measure and control risks more effectively